2020
DOI: 10.1111/tpj.14771
|View full text |Cite
|
Sign up to set email alerts
|

The foxtail millet (Setaria italica) terpene synthase gene family

Abstract: SUMMARY Terpenoid metabolism plays vital roles in stress defense and the environmental adaptation of monocot crops. Here, we describe the identification of the terpene synthase (TPS) gene family of the panicoid food and bioenergy model crop foxtail millet (Setaria italica). The diploid S. italica genome contains 32 TPS genes, 17 of which were biochemically characterized in this study. Unlike other thus far investigated grasses, S. italica contains TPSs producing all three ent‐, (+)‐ and syn‐copalyl pyrophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 103 publications
(181 reference statements)
1
25
0
Order By: Relevance
“…TERPENE SYNTHASES ( TPS ) are involved in terpene biosynthesis. Drought conditions stimulate these TPS genes in various plants, such as pearl millet and tea plants (Karunanithi et al, 2020; Zhou, Shamala, et al, 2020). In a study on lemongrass, SA‐application ameliorates drought stress and induces terpene citral level (Idrees et al, 2010).…”
Section: Secondary Metabolites Role Under Drought Stress In Crop Plantsmentioning
confidence: 99%
“…TERPENE SYNTHASES ( TPS ) are involved in terpene biosynthesis. Drought conditions stimulate these TPS genes in various plants, such as pearl millet and tea plants (Karunanithi et al, 2020; Zhou, Shamala, et al, 2020). In a study on lemongrass, SA‐application ameliorates drought stress and induces terpene citral level (Idrees et al, 2010).…”
Section: Secondary Metabolites Role Under Drought Stress In Crop Plantsmentioning
confidence: 99%
“…Particularly, knowledge of the dynamic networks of plant specialized metabolites that enable plants to adapt to environmental pressures is needed in light of exacerbating crop losses caused by climate shifts and associated pest and disease damage (Savary et al, 2019). Diterpenoids serve as key components of biotic and abiotic stress resilience in rice and maize (Schmelz et al, 2014; Murphy and Zerbe, 2020), and stress-inducible, speciesspecific diterpenoid networks have also been discovered in other food and bioenergy crops such as switchgrass, foxtail millet and wheat, although their physiological functions are less well understood (Wu et al, 2012; Zhou et al, 2012; Schmelz et al, 2014; Pelot et al, 2018; Ding et al, 2019; Karunanithi et al, 2020). Prior studies identified an expansive diTPS gene family in allotetraploid switchgrass that forms specialized diterpenoids both common among the grass family and, to current knowledge, uniquely present in switchgrass (Pelot et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Further modi cation of terpenes involves the introduction of acyl, aryl, or glycosyl groups, usually starting with oxidation catalysed by cytochrome P450 monooxygenases (P450s, also known as CYPs). P450s are ubiquitous in nature and are involved in fundamental biological pathways such as terpene biosynthesis [43][44][45][46]. All these key enzymes were detected by malonyl-enriched modi cations.…”
Section: Discussionmentioning
confidence: 99%